Use of tobacco, nicotine and cannabis products among students in Switzerland - Affolter, Jana; Rohland, Eveline; Philippe, Marc; Tal, Kali; Auer, Reto; Jakob, Julian (Frontiers in Public Health, 2023)
Introduction Most people who smoke cigarettes begin in their teens and teens may also be attracted to new tobacco, nicotine, and cannabis products. We describe use prevalence among upper-secondary school students in Switzerland, including daily use, of tobacco, nicotine, and cannabis products. Methods We invited secondary school students (age 15 to 21) in two Swiss cantons to take an online survey between October 2021 and February 2022. The survey collected demographic information and asked how frequently they used tobacco products (cigarettes in commercial packages, self-rolled cigarettes, hookahs, pipes, cigars and cigarillos, tobacco heating systems, snus, snuff), non-tobacco nicotine products (nicotine pouches, e-cigarettes with and without nicotine), and cannabis products (smoking with and without tobacco, cannabis vaping). Answers were scored on a Likert scale (no use in past month, less than weekly, weekly but not daily, daily use, prefer not to say), then tabulated and reported as descriptive statistics. Results Of 32,614 students in the schools we contacted, 9,515 (29.2%) completed the survey; 49.5% identified as female and 48.4% as male; 9.5% were under 16, 47% were 16–17, 27.5% were 18–19, and 16% were over 19. Reported daily use was most frequent for tobacco cigarettes in commercial packages (14.2%), snus (4.1%) and cannabis smoking with tobacco (3.6%). Most participants (54.8%) reported they had used at least one product at least once within the last month. Conclusion Students who used a product were most likely to smoke cigarettes, but many regularly used new tobacco, nicotine and cannabis products, though use frequency varies.